Evaluation of methods for monitoring air concentrations of hydrogen sulfide - Katarzyna Janoszka; Agata Wziątek; Jan P. Gromiec (Nofer Institute of Occupational Medicine, 2013)
The development of different branches of industry and a growing fossil fuels mining results in a considerable emission of by-products. Major air pollutants are: CO, CO₂, SO₂, SO₃, H₂S, nitrogen oxides, as well as compounds of an organic origin. The main aspects of this paper is to review and evaluate methods used for monitoring of hydrogen sulfide in the air. Different instrumental techniques were discussed, electrochemical, chromatographic and spectrophotometric (wet and dry), to select the method most suitable for monitoring low levels of hydrogen sulfide, close to its odor threshold. Based on the literature review the method for H₂S determination in the air, involving absorption in aqueous zinc acetate and reaction with N,N-dimethylo-p-phenylodiamine and FeCl₃, has been selected and preliminary verified. The adopted method allows for routine measurements of low concentration of hydrogen sulfide, close to its odor threshold in workplaces and ambient air. Med Pr 2013;64(3):449-454